Partially Covered Self-Expandable Metal Stents versus Polyethylene Stents for Malignant Biliary Obstruction: A Cost-Effectiveness Analysis - Alan N Barkun; Viviane Adam; Myriam Martel; Khalid AlNaamani; Peter L Moses (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND/OBJECTIVE: Partially covered self-expandable metal stents (SEMS) and polyethylene stents (PES) are both commonly used in the palliation of malignant biliary obstruction. Although SEMS are significantly more expensive, they are more efficacious than PES. Accordingly, a cost-effectiveness analysis was performed.